MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 020580 BINJAI PADA MATERI LINGKARAN MELALUI METODE PEMETAAN PIKIRAN - Rosliana Rosliana (Universitas Islam Sumatera Utara, 2017)
The purpose of this study is to determine the level of student learning success by applying the method of mind mapping on the subject of the circle and to find out how the implementation of student learning activities by applying the method of mind mapping on the subject of the circle. The subjects of this study are students of SD Negeri 020580 Binjai which consists of 38 students. The tool used to collect data is a test in the form of a description that consists of 10 questions. From the results of data analysis obtained 16 students the success rate is very high, 9 students success rate high, 12 students the success rate is, 1 student success rate is low and no students who not very low success. Based on the data achievement level of student learning outcomes there are 1 students with low success rate and 37 students with high success rate. In terms of learning completeness obtained by the number of students who complete learning (absorbance ≥ 65%) are as many as 37 students (97.37%) and the number of students who are not complete learning (absorption 65%) is as much as 1 student (2.63% ). Based on criteria mastery level and mastery of learning then it can be concluded the level of students of SD Negeri 020580 Binjai is very high. From the results of classroom observation obtained the implementation of good learning activities with active students at every stage of learning activities.